Serum anti-Müllerian hormone concentration before and after salpingectomy for ectopic pregnancy. Issue 5 (November 2018) - Grynnerup, Anna Garcia-Alix; Lindhard, Anette; Sørensen, Steen; Ørskov, Mette; Petersen, Kresten Rubeck; Madsen, Lisbeth Buss; Pilsgaard, Fie; Løssl, Kristine; Pinborg, Anja
Abstract: Research question: Does salpingectomy for ectopic pregnancy affect the ovarian reserve measured by changes in pre- and post-operative levels of anti-Müllerian hormone (AMH)? Design: This is a prospective observational multicentre study of 64 women treated with salpingectomy for an ectopic pregnancy. AMH was measured in serum samples collected at admission before salpingectomy and at follow-up (median time to follow-up [interquartile range] was 3 [3–4] months). Changes in serum AMH levels were investigated using Wilcoxon signed-rank test and the relationship between changes in AMH and age, time to follow-up, and pre-operative serum AMH level was investigated using linear regression analysis. The biological variation of AMH was also calculated. Results: Serum AMH levels did not differ significantly before and after salpingectomy (median ∆AMH [follow-up value minus admission value] 0.40 pmol/l, interquartile range –2.0 to 4.0 pmol/l). ΔAMH was independent of age, time to follow-up and pre-operative serum AMH level. The intra-individual biological variation for AMH ranged from 12.1% to 26.3%, depending on time between the two samples. Conclusions: This is the first paired study to investigate serum AMH values before and after salpingectomy in an unselected population of women presenting with an ectopic pregnancy, including both patients who conceived naturally and following fertility treatment. It was found that salpingectomy for ectopic pregnancy had no short-term effect on serum AMH levels, and changes in AMH levels were independent of age, time to follow-up, and pre-operative serum AMH level. Furthermore, the study demonstrated a 6-month biological variation of AMH of less than 30%.